2015
DOI: 10.7567/jjap.54.024101
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of specific on-resistance for trench gate superjunction MOSFETs

Abstract: The numerical analysis results and theoretical limit of specific on-resistance (RON·A) for a parallel trench gate superjunction (SJ) MOSFET where a striped trench gate structure is parallel to a striped SJ structure and a perpendicular trench gate SJ-MOSFET where the striped trench gate structure is perpendicular to the striped SJ structure are presented. Analytical equations for relationships between breakdown voltage and RON·A are verified by device simulation and show good agreement with simulation results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Super-junction (SJ) structures have been developed to push power semiconductor devices beyond the operating limits of unipolar power devices. [1][2][3][4][5][6][7][8] Si-SJ devices are now widely used up to the 1 kV class, and similar impacts are also expected in the case of SiC SJ devices. Basically, the effect of the SJ structure becomes more prominent with increasing blocking voltage, and the structure will provide a distinct advantage when compared with recently developed Si insulated-gate bipolar transistors (IGBTs) 9,10) for highvoltage applications.…”
Section: Introductionmentioning
confidence: 99%
“…Super-junction (SJ) structures have been developed to push power semiconductor devices beyond the operating limits of unipolar power devices. [1][2][3][4][5][6][7][8] Si-SJ devices are now widely used up to the 1 kV class, and similar impacts are also expected in the case of SiC SJ devices. Basically, the effect of the SJ structure becomes more prominent with increasing blocking voltage, and the structure will provide a distinct advantage when compared with recently developed Si insulated-gate bipolar transistors (IGBTs) 9,10) for highvoltage applications.…”
Section: Introductionmentioning
confidence: 99%
“…2) In addition, superjunction (SJ) structures have been developed in power semiconductor devices in order to outperform the unipolar operating limits. 3,4) In SJ structures, p=n columns are used instead of a unipolar drift layer. It has recently been demonstrated that SJ structures with 25-µm-deep trenches can be fabricated even in wide-band-gap semiconductors such as silicon carbide (SiC).…”
mentioning
confidence: 99%
“…The fabrication of such devices requires the production of trenches and/or apertures. In particular, in the case of SJ structures that are used in Si power devices, to permit unipolar operating limits to be exceeded [8,9], it is necessary to fabricate deep trench structures in an n-type layer with a high depth-to-width aspect ratio that are subsequently backfilled with p-GaN. However, it is difficult to etch deep trenches in GaN.…”
Section: Introductionmentioning
confidence: 99%